The Importance of the De Ritis Ratio and Glasgow Prognostic Score in prehypertensive patients - Ozge Ozcan Abacıoglu; Arafat Yıldırım; Mustafa Doğduş; Ferhat Dindaş; Fethi Yavuz (Acta Medica Alanya)
Aim: To evaluate Glasgow prognostic score (GPS) and De Ritis ratio in optimal blood pressure and prehypertensive patients, and investigate whether these parameters can predict antihypertensive treatment in the follow-up period.Methods: A total of 402 patients who were followed up with a 24-hour ambulatory blood pressure with a pre-diagnosis of hypertension between January 2018 and December 2018 were included in the study. Routine laboratory parameters of the patients were recorded in the hospital digital system. The common health system data of the patients was analyzed until June 2020, and those who were started on antihypertensive treatment were recorded.Results: 402 patients (mean age 40.16 ± 13.01 years, 49% male) were included in the study. 226 of these were in prehypertension group. The mean GPS and the De Ritis ratio, aspartate transferase levels, mean systolic and diastolic blood pressures were different between the groups (p=0.035, p=0.023, p=0.039, p<0.001 and p=0.012, respectively). When patients whose antihypertensive treatment was started and those who did not receive antihypertensive treatment were compared, age, De Ritis ratio and mean diastolic blood pressure differed between the two subgroups (p<0.001, p=0.015 and p=0.040, respectively). Multivariate logistic regression analysis showed that De Ritis ratio and age were, independently, predictors for antihypertensive treatment (OR:3.064, p=0.015 and OR:1.050, p= 0.001 respectively). In ROC curve analysis, both age and De Ritis ratio were successful at predicting the initiation of antihypertensive treatment with an AUC:0.697 and p<0.001 and AUC:0.630 and p=0.018 respectively.Conclusion: Both GPS and the De Ritis ratio were found to be significantly higher in prehypertensive patients than those with optimal blood pressure. Moreover, the De Ritis ratio, an easily calculated laboratory parameter, can be used as a predictive value for antihypertensive treatment.